RIVOJLANMAGAN HOMILADORLIKNING ETIOPATOGENETIK JIHATLARI - Fayzullayeva S.SH.; Usmonova Y.Z.; Navruzova R.S. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Non-developing pregnancy (NP) is one of the most common nosological pathologies in obstetrics and gynecology. Intrauterine death of an embryo in the early stages of development (up to 22 weeks) is called a non-developing pregnancy. Most often this occurs in the first trimester - up to 12 weeks. Non-developing pregnancy is a special form of miscarriage. According to the WHO (1988), the share of non- developing pregnancy in the structure of miscarriage is quite high (10-20%). The frequency of occurrence of non-developing pregnancy according to various data in the first trimester ranges from 15.9% to 16.2%. With age, the frequency of non- developing pregnancy in women increases - from 16.9% in 20-25 years to 20.7% after 40 years.